Contribution of Coffee Farming to Household Income - Amir, Ayu Anisa; Tenriawaru, Nixia; Fudjaja, Letty; Darma, Rahim; Salim, Adriyanto Rahman (AGRITEXTS: Journal of Agricultural Extension, 2023)
This study aims to analyze income and determinants of coffee farming and the contribution against household income in the Tinggimoncong. The location of this study was implemented in the District Tinggimoncong, especially in Parigi, Bontolerung, and Malino, from February until March 2022. The total respondents in this research are 60 farmers. The data was processed using descriptive analysis, analysis percentage, and analysis multiple linear regression with help from the SPSS 22 application. The results of this study show coffee farming contributes to income farming, as well as influencing factors by simultaneous and partial income farming that is a total tree, productivity trees, age plant, cost fixed, cost variables, and output prices as well as in the coefficient test determination proven that no other variables affect income farming. From that result, the author recommends more notice enhancement of efficiency and effectiveness from the variables mentioned before.